Accessibility facilities for people with disabilities at mosques / Ida Shuhada Mohd Ali and Irwan Mohammad Ali - Mohd Ali, Ida Shuhada; Mohammad Ali, Irwan (2019)
The mosque is an Islamic building that has religious and social activities as well as a place where Muslims join together in congregational prayers. In Malaysia there are thousands of mosques built with different designs and ways of construction. However, there are certain of mosques that lack of awareness on the importance of disable people in using it. This research needs to identify accessibility requirement for people with disabilities (PWD's) and to observe the facilities provided and accessibility requirement for PWD's at the mosque in Perak. Quantitative methods were used in this study through the access audit checklist at the selected mosques.